MOLECULAR-STRUCTURES, ELECTROCHEMICAL AND SPECTROSCOPICAL PROPERTIES OF DICHLORODICARBONYLBIS(TRIPHENYLPHOSPHINE)RUTHENIUM(II) AND DICHLORODICARBONYLBIS(TRIPHENYLARSINE)RUTHENIUM(II) - Batista, A. A.; Zukermanschpector, J.; Porcu, O. M.; Queiroz, S. L.; Araujo, M. P.; Oliva, G.; Souza, DHF (Elsevier B.V., 1994)
The cct isomers [RuCl2(CO)2(PPh3)2] (1) and [RuCl2(CO)2(AsPh3)2] (2) were synthesized from [RuCl3(PPh3)2DMA]DMA and [RuCl3(AsPh3)2DMA]DMA, respectively. The complexes were characterized by elemental analysis, IR and UV-vis spectroscopy and their molecular structures were found to be cis-cis-trans isomers by X-ray crystallography. Cyclic voltammetry data show that the triphenylphosphine stabilizes better the ruthenium (II) complex than the triphenylarsine ligand.